Sensational sacrifices delighting the senses in the Bolivian Andes - Stobart, Henry (2018)
Through extensive ethnographic work, Stobart reviews the links between food production and material and intangible culture production. This article is a good example of the theoretical and empirical strength on which his work is based. In it, very suggestively, Stobart examines the multisensory implications of musical reception in the Macha region, north of Potosí, during the holiday periods. With pleasant and acute prose, Stobart reviews the cultural links between music, sexuality and food, as well as between visual and auditory perceptions to finally focus on the relationships between musical practices, religious offerings and the climate of the Potosian region. Taking the notion of synesthesia in anthropology, Stobart analyzes a rich ethnographic material and brings us closer to indigenous conceptions of the Andes hitherto unheard of for us. A text that, without a doubt, will promote similar approaches to the indigenous music of the Peruvian Andes.